Mediasi Kepuasan Kerja dan Stres Kerja pada Hubungan antara Program Jamsostek dan Kinerja Karyawan Studi Kasus pada Perusahaan Swasta di DIY dan Solo - Eny Sulistyowati; Totok Danangdjojo (Universitas Proklamasi 45 Yogyakarta, 2013)
This study aims to explain the influence of the Social Security program on performance and job satisfaction and job stress as a mediating variable. In addition, this study also describes the effect of job satisfaction on the performance and the effect of work stress on performance. The relationship of each variable in this research is to be measured by conducting a survey on 145 employees of private companies that included in Social Security program on DIY and Solo. Then the path analisys used to test the effect of social security program performance in mediation by job satisfaction, performance and job stress, job satisfaction, and examines the effect on the performance and the effect of work stress on performance. The results showed that the social security program significant positively affects job satisfaction and performance. Job satisfaction was also positively and significantly affect performance. Even though mediating role of job satisfaction in the relationship between social security program performance partial. Because merely direct relationship between social security program with greater performance than the mediating role of job satisfaction. Social Security program did not significantly affect the stress of work, as well as job stress did not significantly affect performance. Therefore, the mediating role of work stress on the relationship between social security program with the performance did not occur. Individual differences and work experience may be a factor that causes no significant relationship between the two variables.